The Future of Islamic Law in Sociological Perspective: Challenges of Islamic Law in the Modern Era, Islamic Legal Reform and Global Trends - Yazid, Moh Una; Andaryuni, Lilik (International Journal on Advanced Science, Education, and Religion, 2025)
This study employs a qualitative research design using a socio-legal approach, aiming to analyze Islamic law not merely as normative text but as a social institution that interacts with the dynamics of modern society. Islamic law, which embodies spiritual, moral, and social values, now faces serious challenges in the modern era, particularly due to the secularization of legal and state systems—even in Muslim-majority countries. This secularization often marginalizes Islamic law to the domain of private moral norms, excluding it from formal legal frameworks. Islamic legal reform is an ongoing process responding to the cultural, social, economic, and political dynamics of Muslim communities worldwide. The application of Islamic law in Western contexts such as Europe and the United States serves as a compelling case study in understanding its global future. From a sociological perspective, Islamic law is not a static historical legacy but a living and adaptive system capable of addressing contemporary challenges. Despite pressures from globalization, secular legal systems, and shifting social values, Islamic law continues to inspire collective awareness and calls for substantive reform. These reforms, guided by the maqāṣid al-sharīʿah (objectives of Islamic law), contemporary ijtihād (independent reasoning), and principles of justice and human rights, are moving Islamic law from a textual paradigm to a contextual one. Globalization has also catalyzed broader, more inclusive dialogues about Islamic law.